Effect of Simple Inhalation Therapy to Optimize Airways in Children With Ispa - Lutfiyatul Hilmiah; Tri Sakti Widyaningsih (Jurnal Keperawatan, 2022)
ABSTRACT Respiratory infections are the most common acute diseases in children in various countries, especially in Indonesia. According to WHO (2018), estimates that the incidence of Acute Respiratory Infections (ARI) in developing countries with a mortality rate of toddlers above 40 per 1000 live births is 15-20% per year in the toddler age group. In 2018, the number of deaths in Indonesian toddlers was 151,000, of which 14% of these events were caused by pneumonia. Central Java Province in 2020 ARI reached 67% of risk factors including malnutrition, low excursive breast milk, indoor air pollution, density, low measles immunization coverage. This scientific work is to determine the application of simple inhalation therapy to optimize the airway in children with ARI in Karangdowo Village, Weleri District, Kendal Regency. Case studies using descriptive methods with a case approach in children experiencing ARI with ineffective airways. The sample of this case study was 4 respondents with an age of 3-5 years. Data collection of children with ARI problems using observation sheets and SOPs for simple inhalation therapy. A case study found that before the application of sedrhana inhalation therapy 4 airway respondents were not optimal after the application of simple inhalation therapy that respondents experienced an increase in the airway. After being given simple inhlation therapy, the results of the study showed that of the 4 respondents who were carried out therapy showed optimal airway.